Fluoroalkyl end‐capped oligomers possessing nonflammable characteristic in calcium carbonate nanocomposites. (22nd March 2013) - Saito, Tomoya; Kakehi, Hiroshi; Kato, Yoshihiro; Miura, Masashi; Isu, Norifumi; Sawada, Hideo
<x xml:space="preserve">Abstract</x> Calcium chloride reacted with sodium carbonate in the presence of a variety of fluoroalkyl end‐capped oligomers such as fluoroalkyl end‐capped acrylic acid oligomer (RF‐[ACA]n‐RF), 2‐methacryloyloxyethanesulfonic acid oligomer (RF‐[MES]n‐RF), N, N‐dimethylacrylamide oligomer (RF‐[DMAA]n‐RF) and acryloylmorpholine oligomer (RF‐[ACMO]n‐RF) to afford the corresponding fluorinated oligomers/calcium carbonate composites. Each fluorinated oligomer/calcium carbonate composite thus obtained is nanometer size‐controlled very fine particles (25–114 nm) possessing a good dispersibility and stability in a variety of solvents including water. Thermal stability of these fluorinated calcium carbonate nanocomposites was studied by thermogravimetic analyses measurements. Fluorinated oligomes, in which the theoretical oligomer content in the composites is 19%, were able to give no weight loss corresponding to the content of oligomer in each case even after calcination at 800 °C. On the other hand, a slight weight loss corresponding to the contents of oligomers in the composites after calcination at 800 °C was observed in RF‐(MES)n‐RF/, RF‐(DMAA)n‐RF/ and RF‐(ACMO)n‐RF/calcium carbonate nanocomposites, in which the theoretical contents of the oligomers were 36–53%, although RF‐(ACA)n‐RF/calcium carbonate nanocomposites gave a clear weight loss corresponding to the contents of oligomer under similar conditions. Fluorinated oligomers/calcium carbonate nanocomposites possessing no weight loss at 800 °C were applied to the surface modification of poly(methyl methacrylate) (PMMA) to exhibit a good oleophobicity imparted by fluorines on the surfaces. Interestingly, these fluorinated calcium carbonate nanocomposites after calcination at 800 °C were found to exhibit the similar oleophobic characteristic on the modified PMMA surfaces as well as that of the nanocomposites before calcination. Copyright © 2013 John Wiley & Sons, Ltd.